Aerobic Exercise Practiced Over Time Mitigates the Structural Effects on the Vascular System Caused by the Deleterious Effects of Aging - Nicoletti, Rafael Antunes [UNESP]; de Souza, Thiago Pereira [UNESP]; Miotto, Danyelle S. [UNESP]; Duchatsch, Francine [UNESP]; Tardelli, Lidieli Pazin [UNESP]; de Paula, Vinicius Ferreira [UNESP]; Amaral, Sandra Lia [UNESP]; Zago, Anderson Saranz [UNESP] (Taylor & Francis, 2025)
Background: Aerobic training has been considered beneficial for determining the detrimental alterations in blood vessels caused by aging. Objective: Evaluate the relationship between the preventive effects of aerobic exercise and time of practice on cardiovascular health, in aged Wistar rats. Methods: Wistar rats (16 months) were divided into 3 groups: (1) sedentary (AGED); (2) long-term trained\61 weeks (LTT); and (3) short-term trained\final 8 weeks of life (STT). Body weight, maximum physical capacity, systolic blood pressure (SBP), pulse wave velocity (PWV), plasma nitrite (NO), oxidative stress (TBARS), wall thickness, the wall-to-lumen ratio, and collagen of the thoracic aorta, carotid, and femoral arteries were measured. Results: Both trained groups showed an increase in physical capacity when compared to the AGED group (p=<0.001 for LTT and p=0.011 for STT), and the LTT group demonstrated higher values when compared to the STT group (p= 0.004). The LTT group presented attenuation of PWV (p= 0.002) and a reduction in the wall thickness and wall-to-lumen ratio of the thoracic aorta (p=0.032 and 0.008, respectively) and carotid arteries (p=0.019 and 0.012, respectively) when compared to the AGED group. The STT group presented a reduction in TBARS compared to the AGED group (p=0.046). Additionally, both trained groups (LTT and STT) presented a reduction in the percentage of arterial collagen compared to the AGED group in the thoracic aorta (p=<0.001 and p=0.001 respectively) and carotid arteries (p= <0.008 and p= 0.041 respectively). Conclusion: This study demonstrated that long-term training decreased the level of collagen, PWV values, wall thickness, and the wall-to-lumen ratio of the aorta and carotid arteries compared to the AGED group. Moreover, short-term training reduced TBARS and collagen percentage in the aorta and carotid arteries compared to the AGED group.
Keywords: aerobic training; aging; arteries; collagen deposition; pulse wave velocity